Gender and right-wing populism in the Low Countries: ideological variations across parties and time - de Lange, Sarah L.; Mügge, Liza M. (Patterns of prejudice, 2015)
Although scholarship on the general ideological orientation of right-wing populist parties is well established, few scholars have studied their ideas about gender. De Lange and Mügge therefore ask how differences in ideology shape right-wing populist parties' ideas on gender. Drawing on the qualitative content analysis of party manifestos, they compare the gender ideologies and concrete policy proposals of national and neoliberal populist parties in the Netherlands and Flanders from the 1980s to the present. They find that some parties adhere to a modern or modern-traditional view, while others espouse neo-traditional views. Moreover, some right-wing populist parties have adopted gendered readings of issues surrounding immigration and 'Islam', while others have not. The variation in stances on 'classical' gender issues can be explained by the genealogy and ideological orientation of the parties, whereas gendered views on immigration and Islam are influenced by contextual factors, such as 9/11.